SAT0025 Cxcl4 alters transcriptomic and epigenetic imprinting of dendritic cells thereby driving fibrosis through extracellular matrix formation. (12th June 2018) - SIlva-Cardoso, S.C.; Tao, W.; Angiolilli, C.; Lopes, A.P.P.; Bekker, C.; van Laar, J.; Hack, E.; Boes, M.; Pandit, A.; Radstake, T.R.D.J.
Abstract : Background: Aberrant accumulation of extracellular matrix (ECM) in multiple organs or fibrosis is one of the three hallmarks that characterises the pathogenesis of systemic sclerosis (SSc), together with immune dysregulation and small vessel vasculopathy. Recent studies have shown that CXCL4 (Chemokine CXC motif ligand 4) levels are increased in patients with SSc and correlated with skin and lung fibrosis. 1 CXCL4 plays key role in physiological processes, although it has been also implicated in several pathological conditions such as autoimmune diseases and cancer. We and others have shown that CXCL4 modulates the phenotype and function of immune cells 2, suggesting a critical role of this chemokine in innate and adaptive immune responses. However, how CXCL4 exactly modulates immune cell responses remains unclear. Objectives: Here we investigated the impact of CXCL4 exposure on the transcriptome and DNA methylation of monocyte-derived dendritic cells (moDCs), and the consequence on their function. Methods: We differentiated human moDCs in the presence of CXCL4. After 6 days differentiation, cells were stimulated with a TLR3 ligand (polyI:C) as described in our previous study. 2 RNA sequencing and DNA methylation profiling was performed at various time points during differentiation and stimulation. Results: Integration of high-throughput analyses of RNA sequencing and DNA methylation reveals that CXCL4 drives to dramatic changes on the transcriptome and epigenome levels. This is reflected in the dysregulation of critical innate and adaptive immune pathways, like antigen presentation, and cytokine signalling. For the first time, we show that CXCL4 potentiates a novel function to dendritic cells, namely, the production of ECM molecules, such as fibronectin (FN1) and osteopontin (OPN). Furthermore, we also found that CXCL4 exposure results in epigenetic imprinting during moDC differentiation. Using novel bioinformatic methods, we have found that CXCL4 mediates the altered cell function via key transcriptional regulators. Conclusions: This study provides better understanding how CXCL4 affects moDCs through several immune and non-immune pathways and shows for the first time the direct implication of CXCL4 on the production of ECM by inflammatory cells, thereby underscoring the pivotal role of CXCL4 in inflammatory and fibrotic conditions such as SSc. References: [1] L. van Bon, Affandi AJ, et al. Proteome-wide analysis and CXCL4 as a biomarker in systemic sclerosis. N. Engl. J. Med2014. doi:10.1056/NEJMoa1114576 [2] Silva-Cardoso SC, Affandi AJ, et al. CXCL4 Exposure Potentiates TLR-Driven Polarization of Human Monocyte-Derived Dendritic Cells and Increases Stimulation of T Cells. J. Immunol2017. doi:10.4049/jimmunol.1602020 Acknowledgements: This study was supported by the: PhD fellowship SFRH/BD/89643/2012 from the Portuguese Funda&x00C7;&x00E3;o para a Ci&x00EA;ncia e a Tecnologia (FCT) to Sandra C. Silva-Cardoso; China Scholarship Council (CSC) fellowship No. 201606300050 to Weiyang Tao; ERC starting grant (CIRCUMVENT) and Arthritis foundation grant to Timothy R.D.J. Radstake. Disclosure of Interest: None declared